Studi Pemodelan Tipomorfologi Kampung Sunda: Studi Kasus Kampung Sehati Desa Nagrog Kecamatan Cicalengka Kabupaten Bandung - Sela Renika; Weishaguna; Saraswati (UNISBA Press, 2022)
Abstract. This study was preceded by the existence of phenomena that exist in the Sehati village, namely the interest in the Bandung district policy of applying 1000 Sundanese cultural preservation villages, the interest of exposing the uniqueness of the Kendan Tatar culture in the physical form of the Sundanese village and the existence of Sundanese village embryos in the Nagrog village but not yet conceptualized according to the theme of cultural preservation. So this study focuses on the question